Diseño del manual de procedimientos de facturación en la IPS Somid SAS Costa de Coveñas, Sucre (2023)
Every entity that provides health services in Colombia must follow the guidelines established by the Ministry of Health and Social Protection of Colombia and, in order to be more competitive, they must aim to obtain health accreditation, seeking excellence in the services provided and committing their human resource in compliance with one of the standards established by the National Government in the Ambulatory and Hospital Health Accreditation Manual of Colombia according to resolution 5095 of. Therefore, it is necessary to design procedures that comply with the standards established by the Ministry, especially in the area of billing, which is the financial backbone of any entity that provides health services; procedures that guarantee timely communication with the entities that generate the payments for the services offered. Therefore, this study presents the design of the Billing Procedures Manual of the IPS SOMID SAS COSTA of Coveñas-Sucre, which is considered a necessary tool for the continuous improvement of the IPS processes, directing it towards accreditation in compliance. of Standard 142 of the Ambulatory and Hospital Accreditation Manual in Colombia.